Prevalence and Risk Factors of Functional Constipation According to the Rome Criteria in China: A Systematic Review and Meta-Analysis - Chen, Zhe; Peng, Yingying; Shi, Qingyang; Chen, Yongjie; Cao, Lujia; Jia, Jiannan; Liu, Chunxiang; Zhang, Junhua (Frontiers in Medicine, 2022)
Background: Functional constipation (FC) is a common bowel disorder that prevails worldwide. In China, although a heterogeneous prevalence of constipation is expected, it is currently not demonstrated. In this study, we aimed to evaluate the prevalence and related risk factors of FC in the Chinese population, according to the Rome criteria. Methods: We searched the PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang Data Knowledge Service Platform, and VIP information resource integration service platform databases from database inception to July 2021. Population-based cross-section studies that enrolled adults with FC, diagnosed by the Rome criteria, were deemed eligible. We summarized the overall prevalence and detected the subgroup effect per the Rome I, Rome II, Rome III, and Rome IV criteria. We used the generalized linear mixed model with a random-effect intercept to pool the prevalence and performed pairwise meta-analyses for prevalence comparisons by risk factors. Results: We identified 3213 records through our database search, and 39 studies from China, comprising 124079 participants, met the eligibility criteria for our study. The pooled overall prevalence of FC using the Rome criteria was 8.5% in China. Heterogeneous prevalence was detected within the Rome criteria (Rome II: 10.6%, 95%CI: 7.2–15.4; Rome III: 6.5%, 95%CI: 3.4–12.0; Rome IV: 8.1%, 95%CI: 5.6–11.8). The prevalence increased between 1991 (5.5%, 95%CI: 3.6–8.2) to 2020 (10.9%, 95%CI: 5.5–20.4). Higher prevalence was found in females (OR=1.53, 95%CI: 1.31–1.78) and the elderly (≥70 years vs ≤ 29 years: OR= 3.38, 95%CI: 2.16–5.30) than in males and the younger population. A high-fiber diet was associated with lower prevalence (OR=0.33, 95%CI: 0.15–0.75), whereas irregular bowel habit and inactivity were associated with higher prevalence (OR=3.64, 95%CI: 2.64–5.03; OR=1.97, 95%CI: 1.14–3.43). Unhealthy mental states, such as anxiety and depression, and poor sleep quality led to high prevalence (OR= 3.16, 95%CI: 1.96–5.11; OR= 2.74, 95%CI: 1.76–4.26; OR= 2.14, 95%CI: 1.69–2.72, respectively). Conclusion: FC prevails variously in China regarding the different Rome criteria, and personal characteristics and habits. The prevalence also increased over the past three decades. FC should be included under the primary care setting with uniform diagnosis criteria in China.